Bell Beaker or not Bell Beaker: an perspective on chalcolithic at the iberian peninsula paired fingernail imprints in s-shaped vessels - Basílio, Ana Catarina (2020)
The Bell Beaker phenomenon is the sum of several regional answers. Those are diluted into a reality with several shared characteristics. Nevertheless, and although being one of the most studied expressions of the European Recent Prehistory, more specific adaptations are still to be understood. This is the case of the paired fingernail imprints, or pinched motifs, that due to their scarceness are mostly unnoticed in Iberia. However, one was able to highpoint a scarceness of these standardised motifs in funerary contexts and a concentration in contexts dated from the last quarter of the IIIrd millennium BC, in the precise period of transition in the way of life of the peninsular human groups. Also, the regression in the communicative ability of the vessels, but at the same time dear links with other European Bell Beaker contexts seems to strengthen the hypothesis that this large-scale style must be understood as another agent in the ongoing identarian and social processes acting, as such, in the transition to the beginning of the Peninsular Bronze Age.